Impact of Latin American public transport systems on urban mobility and the environment (Publicaciones en Ciencias y Tecnología, 2019)
Latin American cities have spread in the last three decades causing greater need for mobility and transportation of masses of people, being a pillar in the economic and social development of the main cities; however they bring with them negative effects. The present work identifies and describes these negative effects on society and the environment in Latin American countries, through a descriptive-documentary work, supported by the literature review on mobility and transport systems of the main Latin American cities, in addition to the review of data published by OLADE, WHO and CAF for each unwanted effect to consider. As a result, only 0.43% of the total roads are for the circulation of cyclists and pedestrians; the bus is the main mode of transportation; the largest numbers of daily trips are made by public transport, the highest energy consumption and CO2 emission is attributed to individual transport, and 69% of transport accidents occur in urban settings. The subway is the one with least negative social and environmental impact. The high death rates from road accidents and high consumption of electrical energy represent the most important impacts caused by public transport systems.
Keywords: Urban mobility; public transport; Latin America; energy consumption; negative effects